KC Pekarna – Maribor Squat - Virant, Zala (Journal for Geography, 2019)
The squatting zones are a constituent part of every major modern city and are a consequence of social differentiation. These areas have a special role in urban environment as they represent the main location for alternative cultural production. In Maribor, the alternative scene is located on the premises of Kulturni center Pekarna. In this article we study the creation and the development of Maribor’s squat, its exterior properties, activities that are currently taking place and the structure of social group that visits the squat. Kulturni center Pekarna is a place of difference, novelty and alternative that has a special role in an urban setting and a special meaning for individuals that are part of alternative culture.
Keywords: squat; Cultural center Pekarna; Maribor; social-spatial differentiation; alternative scene